2010
DOI: 10.1111/j.1440-1584.2010.01134.x
|View full text |Cite
|
Sign up to set email alerts
|

Genital chlamydia in southern New South Wales: An ecological analysis of testing and notification patterns 2004–2008

Abstract: The low proportion of tests performed to presentations (in conjunction with the high proportion of notifications to tests performed) reflects that chlamydia testing among providers is still being undertaken in a targeted approach rather than from a population-focused screening perspective. Further work with GPs is required to improve chlamydia screening rates, and ensure practice is consistent with national guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…A statistician, located at a site away from the clusters, generated the randomisation sequence using a computer-generated minimisation algorithm. The algorithm aimed to achieve balance for three pre-specified variables: i) estimated chlamydia prevalence (<3% vs. ≥3%, based on an earlier study); 11 ii) chlamydia testing rate (<6% vs. ≥6% based on data from rural primary care clinics in 2008); 12 and iii) number of 16 to 29 year olds in the town (<2000 vs. ≥2000, the 75th percentile of population size in eligible postcodes). The statistician ran the randomisation algorithm after the baseline estimation of chlamydia prevalence in each cluster and informed research staff of the allocation who in turn notified clinics.…”
Section: Randomisation and Maskingmentioning
confidence: 99%
“…A statistician, located at a site away from the clusters, generated the randomisation sequence using a computer-generated minimisation algorithm. The algorithm aimed to achieve balance for three pre-specified variables: i) estimated chlamydia prevalence (<3% vs. ≥3%, based on an earlier study); 11 ii) chlamydia testing rate (<6% vs. ≥6% based on data from rural primary care clinics in 2008); 12 and iii) number of 16 to 29 year olds in the town (<2000 vs. ≥2000, the 75th percentile of population size in eligible postcodes). The statistician ran the randomisation algorithm after the baseline estimation of chlamydia prevalence in each cluster and informed research staff of the allocation who in turn notified clinics.…”
Section: Randomisation and Maskingmentioning
confidence: 99%
“…General practice is also where the majority of chlamydia diagnoses in Australia are made. 13 Current Australian guidelines for chlamydia screening in general practice recommend annual testing of all sexually active people aged 15-29 and patients with a recent change in partner or reporting inconsistent condom use. 14 A study of Australian general practitioners (GPs) found that chlamydia testing was occurring in 0.32% of patient encounters overall; however, in an age group most relevant to screening (age [15][16][17][18][19][20][21][22][23][24], tests were being performed in 1.32% of encounters.…”
mentioning
confidence: 99%